Addendum ai lessici di Alcyone: il Vocabolario del Carena - Donatella Martinelli (Annali Online dell'Università di Ferrara. Sezione Lettere)
This essay focuses on the D’Annunzio lessicographic tools already examined in the past by Franco Gavazzeni and his school. New important data have been collected after these first investigations. The dictionary we add to (descendant of the famous Giacinto Carena’s Vocabolario domestico) relates to a poem, l’Otre, wich is per se an encyclopedia of the languages and styles used in Alcyone.